Revision of the Siriella brevicaudata species group (Crustacea: Mysida: Mysidae) from the West Indo-Pacific - Daneliya, Mikhail; Price, W. Wayne; Heard, Richard W. (European Journal of Taxonomy, 2018)
The Siriella brevicaudata species group from the West Indo-Pacific, defined and designated by Murano & Fukuoka (2008), previously contained five nominal species. In this study we describe five new species in the brevicaudata group: S. bassi sp. nov. from the Bass Strait, southern Australia, S. occulta sp. nov. from the Arabian Gulf, S. muranoi sp. nov. from the coast of Northern Territory, Australia, S. tabaniocula sp. nov. from Ningaloo Reef of Western Australia and Lodestone Reef off Queensland, and S. talbotae sp. nov. from Lizard Island, Queensland, Australia. Furthermore, Siriella hanseni W.M. Tattersall, 1922 from India and S. vincenti W.M. Tattersall, 1927 from South Australia are redescribed based on re-examination of their type material. A re-examination of specimens subsequently attributed to these two species from other geographical regions showed that these were misidentifications, partly representing three of the new species described herein. Siriella gibbosa (Ledoyer, 1970), which was previously synonymized with S. brevicaudata Paulson, 1875 by Bačescu, is revalidated and included within the brevicaudata group. Siriella lacertilis Talbot, 2009, from Lizard Island, is placed within the brevicaudata group. Diagnostic features for all the members of the group and the group itself are updated. As a result of the present study, the brevicaudata group now comprises 12 valid species.